1983
DOI: 10.1099/00221287-129-9-2753
|View full text |Cite
|
Sign up to set email alerts
|

The Production of F41 Fimbriae by Piglet Strains of Enterotoxigenic Escherichia coli that Lack K88, K99 and 987P Fimbriae

Abstract: The enterotoxigenic Escherichia coli strains 1676,1706,175 1 and KEC96a, which do not produce fimbrial adhesive antigens of the K88, K99 or 987P antigen type reacted both in vitro and in vivo with antiserum to F41 fimbriae in an indirect immunofluorescent antibody technique. Antiserum used to demonstrate material B, an adhesive antigen thought to mediate the adhesive and mannose-resistant (MR) haemagglutinating properties of E. coli strains 1676, 1706 and 1751, reacted in vitro with an F41+ strain. The antiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…F41 antigen has been found in the bovine reference ETEC strain B41 (De Graaf & Roorda, 1982;Morris et al, 1983). It mediates bacterial adherence to intestinal epithelial cells (Morris et al, 1983), but its exact role in pathogenicity is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F41 antigen has been found in the bovine reference ETEC strain B41 (De Graaf & Roorda, 1982;Morris et al, 1983). It mediates bacterial adherence to intestinal epithelial cells (Morris et al, 1983), but its exact role in pathogenicity is not known.…”
Section: Discussionmentioning
confidence: 99%
“…It mediates bacterial adherence to intestinal epithelial cells (Morris et al, 1983), but its exact role in pathogenicity is not known. In this report, a genetic approach to the problem, especially by obtaining F41-variants, has shown that the F41 antigen is an important virulence factor in an infant mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, F41 production has been demonstrated in non-K99-producing strains of ETEC of serogroup 0101 isolated from piglets with diarrhea (15). These strains have been demonstrated to be fully virulent in experimental infections in piglets and calves (1,15,21). This suggests that F41 is a virulence factor, since these strains produce no other known adhesin.…”
mentioning
confidence: 99%
“…The F41 antigen was first recognized as a second mannoseresistant hemagglutinin produced by ETEC strains which also express the K99 adhesin (14). The F41 antigen is associated with K99-producing ETEC of serogroups 09 and 0101, but has not been reported among K99-producing strains of other serogroups (15). Recently, F41 production has been demonstrated in non-K99-producing strains of ETEC of serogroup 0101 isolated from piglets with diarrhea (15).…”
mentioning
confidence: 99%
“…ETEC strains with different fimbriae have been isolated from pigs with diarrhoea, including F4 (Jones and Rutter, 1972), F18 (Bertschinger et al, 1990), 987P , K99 and F41 (Morris et al, 1983). These bacteria adhere to brush borders of the intestinal epithelial cells through their surface fimbriae.…”
Section: Introductionmentioning
confidence: 99%